Relationship between perceived usefulness and online shopping behaviour among university students / Mohamad Shazwan Shauqi Ithnin, Nor ‘Ain Abdullah and Mohd Lutfi Iskandar - Ithnin, Mohamad Shazwan Shauqi; Abdullah, Nor ‘Ain; Iskandar, Mohd Lutfi (Faculty of Business and Management, 2022)
E-marketers can now reap the benefits of the increasing use of the Internet in Malaysia. Such marketers understand a factor that influences online shopping behaviour among students while maintaining their existing online customers, which is vital to developing their marketing strategies. The purpose of this study is to investigate the role of perceived usefulness that influence online shopping behaviour among university students. As for methodology, primary data was collected from a sample size of 276 students at private University in Shah Alam using survey instruments. The collected data was analysed using SmartPLS. The findings revealed that perceived usefulness have positive relationship on online shopping behaviour among university students. This research also includes a discussion, limitations, recommendations, and conclusions.